Efficiency Enhancement of Cocktail Dye of Ixora coccinea and Tradescantia spathacea in DSSC. (17th December 2015) - Zolkepli, Zularif; Lim, Andery; Ekanayake, Piyasiri; Tennakoon, Kushan
Abstract : The use of anthocyanin dyes extracted from epidermal leaves of Tradescantia spathacea (Trant) and petals of Ixora coccinea (IX) was evaluated in the application of dye-sensitized solar cells (DSSCs). Subsequently, cocktail anthocyanin dyes from these dyes were prepared and how they enhanced the cell's overall performance was assessed using five different volume-to-volume ratios. Cocktail dyes absorbed a wider range of light in the visible region, thus increasing the cell efficiencies of the cocktail dyes when compared to the DSSC sensitized by individual dyes. The surface charge (zeta-potential), average size of aggregated anthocyanin molecules (zetasizer), and anthocyanin stability in different storage temperatures were analyzed and recorded. Lower size of aggregated dye molecules as revealed from the cocktail dyes ensured better adsorption onto the TiO2 film. Tradescantia / Ixora pigments mixed in 1 : 4 ratio showed the highest cell efficiency ofη = 0.80 %, under the irradiance of 100 mW cm −2, with a short-circuit current density 4.185 mA/cm 2, open-circuit voltage of 0.346 V, and fill factor of 0.499. It was found that the desired storage temperature for these cocktail dyes to be stable over time was −20°C, in which the anthocyanin half-life was about approximately 1727 days.